Commitment, interpersonal stigma, and mental health in romantic relationships between transgender women and cisgender male partners. (July 2019) - Gamarel, Kristi E.; Sevelius, Jae M.; Reisner, Sari L.; Coats, Cassandra Sutten; Nemoto, Tooru; Operario, Don
The goals of this study were to (a) examine associations between interpersonal stigma and psychological distress among a sample of transgender women and their cisgender male partners and (b) identify whether commitment moderates the association between interpersonal stigma and psychological distress. To address these aims, 191 couples consisting of transgender women and their cisgender male partners completed a one-time survey. Actor–partner interdependence models were fit to examine stigma, commitment, and their interaction on psychological distress. More frequent experiences of interpersonal stigma were associated with elevated psychological distress for both partners. For transgender women, higher commitment was associated with lower psychological distress. There was a significant interaction effect such that the association between interpersonal stigma and psychological distress was attenuated by greater commitment for transgender women but not for their cisgender male partners. Findings provide preliminary support for associations between interpersonal stigma and mental health of both partners and identify commitment as a potential stress buffer for transgender women.